Genome-wide comparative analysis of H3K4me3 profiles between diploid and allotetraploid cotton to refine genome annotation - Qi You (Nature Portfolio, 2017)
Abstract Polyploidy is a common evolutionary occurrence in plants. Recently, published genomes of allotetraploid G. hirsutum and its donors G. arboreum and G. raimondii make cotton an accessible polyploid model. This study used chromatin immunoprecipitation with high-throughput sequencing (ChIP-Seq) to investigate the genome-wide distribution of H3K4me3 in G. arboreum and G. hirsutum, and explore the conservation and variation of genome structures between diploid and allotetraploid cotton. Our results showed that H3K4me3 modifications were associated with active transcription in both cottons. The H3K4me3 histone markers appeared mainly in genic regions and were enriched around the transcription start sites (TSSs) of genes. We integrated the ChIP-seq data of H3K4me3 with RNA-seq and ESTs data to refine the genic structure annotation. There were 6,773 and 12,773 new transcripts discovered in G. arboreum and G. hirsutum, respectively. Furthermore, co-expression networks were linked with histone modification and modularized in an attempt to explain differential H3K4me3 enrichment correlated with changes in gene transcription during cotton development and evolution. Taken together, we have combined epigenomic and transcriptomic datasets to systematically discover functional genes and compare them between G. arboreum and G. hirsutum, which may be beneficial for studying diploid and allotetraploid plants with large genomes and complicated evolution.